A Note on the Generalized Nonlinear Vector Variational-Like Inequality Problem. (28th July 2021) - Gupta, Ankit; Kumar, Satish; Sarma, Ratna Dev; Garg, Pankaj Kumar; George, Reny
Abstract : In this paper, we discuss two variants of the generalized nonlinear vector variational-like inequality problem. We provide their solutions by adopting topological approach. Topological properties such as compactness, closedness, and net theory are used in the proof. The admissibility of the function space topology and KKM-Theorem have played important role in proving the results.